Out‐of‐hospital cardiac arrests in nursing homes and primary care facilities in Pirkanmaa, Finland. Issue 9 (29th May 2018) - Kangasniemi, H.; Setälä, P.; Huhtala, H.; Kämäräinen, A.; Virkkunen, I.; Jämsen, E.; Yli‐Hankala, A.; Hoppu, S.
Abstract : Background: Dispatching Emergency Medical Services to treat patients with deteriorating health in nursing homes and primary care facilities is common in Finland. We examined the cardiac arrest patients to describe this phenomenon. We had a special interest in patients for whom cardiopulmonary resuscitation was considered futile. Methods: We conducted an observational study between 1 June 2013 and 31 May 2014 in the Pirkanmaa area. We included cases in which Emergency Medical Services participated in the treatment of cardiac arrest patients in nursing homes and primary care facilities. Results: Emergency Medical Services attended to a total of 355 cardiac arrest patients, and 65 patients (18%) met the inclusion criteria. The included patients were generally older than 65 years, but otherwise heterogeneous. Nineteen patients (29%) had a valid do‐not‐attempt‐resuscitation order, but paramedics were not informed about it in 10 (53%) of those cases. Eight (12%) of the 65 patients survived to hospital admission and 3 (5%) survived to hospital discharge with a neurologically favourable outcome. Two patients were alive 90 days after the cardiac arrest; both were younger than 70 years of age and had ventricular fibrillation as primary rhythm. There were no survivors in nursing homes. Conclusions: The do‐not‐attempt‐resuscitation orders were often unavailable during a cardiopulmonary resuscitation attempt. Although resuscitation attempts were futile for patients in nursing homes, some patients in primary care facilities demonstrated a favourable outcome after cardiac arrest. Emergency Medical Services seem to be able to recognise potential survivors and focus resources on their treatment.